Application of hot water and cold air to reduce bacterial contamination on broiler carcasses - Beterams, Anja; Kirse, Alina; Kreienbrock, Lothar; Stingl, Kerstin; Bandick, Niels; Reich, Felix (Frontiers in Microbiology, 2024)
Two Different physical treatments (heat via water bath and cold air) with various temperatures (20/70/75/80 °C and -80/-90 °C) and exposure times (20, 30, 40 s) were carried out to identify a decontaminating effect on zoonotic pathogens on broiler carcasses. Subsequently, carcasses were analyzed for thermotolerant Campylobacter (C.), Salmonella, Escherichia (E.). coli and total colony count (TCC). Moreover, for the hot water treatment, qPCR with viable/dead differentiation (v-qPCR) was applied to detect viable but non-culturable cells (VBNC) of Campylobacter, referred to as intact but putatively infectious units (IPIU). Hot water immersion was tested on carcasses inoculated with C. jejuni and Salmonella, while cold air treatment was evaluated for naturally contaminated carcasses of broiler flocks colonized with Campylobacter.For hot water treatment, the statistically significant reducing effect was about 1 log10 CFU/ml for both Salmonella and Campylobacter for 70 -80 °C and 20/30 s treatments. The effect of heat treatment for Campylobacter was smaller when samples were analyzed with v-qPCR with reductions of 0.5 -0.8 log10 IPIU/ml in mean. Cold air treatments at -90 °C were effective in reducing the mean contamination level of Campylobacter by 0.4 -0.5 log10 CFU/ml at all exposure times (p < 0.05).Hot water treatments showed a decreasing trend on TCC by 0.6 -0.9 log10 CFU/ml (p < 0.05). TCC counts were not significantly affected by cold air treatment. For E. coli no statistically significant reductions were observed by hot water treatment. The cold air treatment at -90 °C for 20 and 40 s led to a reduction of E. coli by 0.4 and 0.8 log10 CFU/ml (p < 0.05), respectively. Treatment of carcasses with higher bacterial levels tended to show higher reduction.The research demonstrated that the efficacy of physical treatments for decontamination of broiler carcasses was more pronounced for hot water immersion than for cold air exposure. In conclusion, the results shed light on the potential application of these physical treatments in practice to reduce the quantitative load of contaminating pathogens to enhance food safety in the broiler meat production.